L'enfant des steppes dans l'imagerie et la littérature soviétique pour enfants (1917-1953) - Daria Sinichkina (Strenae)
From the October Revolution of 1917 to the death of Stalin in 1953, the considerations of realpolitik, as much as its ideology, were projected onto the image of non-native children of the USSR. The internationalist era that saw the appearance of happy children exploring a new world in images from magazines, books and newspapers was quickly followed by a systematization of representations: children went from being undifferentiated to being "equal," united in the fixed symbol of the young pioneer, the red scarf. However, in the 1930s, a radically different representation of the non-native child emerged, transformed by propaganda into a cynical and corrupted incarnation of the socialist utopia.